DEVELOPING INQUIRY LEARNING-BASED ENGLISH INSTRUCTIONAL MATERIALS FOR THE SEVENTH GARDE OF JUNIOR HIGH SCHOOL - Devi Safitri; Sitti Nurpahmi; Djuwairiah Ahmad (ELTIES : English Language Teaching for EFL Learners, 2020)
This  research is aimed  to developing instructional English materials for the students of the seventh grade especially in basic competencies 3.5, 4.5, 3.6, and 4.6 at  MTs  Madani  Pao-pao  based  on  2013  curriculum  supported  by  using  inquiry  learning  model  and  using  the concept of HOTS in indicators achieved. The research design used in this study was Research and Development (R&D).  The   development   model   used   was   ADDIE   model. It consists of need analysis, design, development, implementation, and evaluation. The  procedures  included  analyzing  materials   needed   by spreading  questionnaire  to  the  students  and  analyzing  the  basic   competencies used, designing a  blueprint  of  materials and the instructional materials, and validating the material by the expert. There were 146 students as the respondents of 26 questionnaire questions. The instruments used in this research were the documents, questionnaire, and validation checklist. In this research, the expert was involved in order to validate the product. There were three systematic  aspects  that  they  validated  of  the product:  Materials  Systematic  Organization,  Systematic  English   Teaching  and  Systematic  Content  of  English.  Therefore,  the  result  indicated  that  based on experts judgment as well as  product  development  result,  the  developed basic competency  3.5  &  4.5  and  basic  competency  3.6  &  4.6  were applicable to be taught at the seventh grade students  of  Junior  High  School as topic in English for them.